12x-3(-6+4x)=12

Simple and best practice solution for 12x-3(-6+4x)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-3(-6+4x)=12 equation:


Simplifying
12x + -3(-6 + 4x) = 12
12x + (-6 * -3 + 4x * -3) = 12
12x + (18 + -12x) = 12

Reorder the terms:
18 + 12x + -12x = 12

Combine like terms: 12x + -12x = 0
18 + 0 = 12
18 = 12

Solving
18 = 12

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -4x+1=10 | | 1/6x100 | | (2z-1)/z | | (6/5)(5-4g)=-18 | | 14x-6=-12 | | 7m+10= | | 2x-2(x-2)=14 | | y=1/7(-3)-4 | | 8a+72=8a-40 | | 7/35x100 | | 4+65x=52x+10 | | 2z-1/z | | 63p-16p^2=17p+58p^2 | | y=1/7(-4)-4 | | 2(7)-6=2(4) | | N+5.9=-2.1 | | f(x)=x^3-16x | | 3.3-2y=8 | | 6b+14=-7-5b+4b | | 3y=54-6(7) | | x-4.6=3.7 | | 5y^2-3y^2=72y+9y | | 2x-6=2(18-2x) | | 5=w+1.5 | | 8x+6(2x-4)=42 | | -x+7=-2x | | 3x*2/7 | | 5x-2=-32x+35 | | Y-13=29 | | 8x+-5y=13 | | 8(4-u)+u+u+u=8+u | | 2x+4=67 |

Equations solver categories